2008
DOI: 10.1152/ajpgi.90294.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-3 stimulates survival of goblet cells in organotypic cultures of fetal human colonic epithelium

Abstract: Cells within the normal human colonic epithelium undergo a dynamic cycle of growth, differentiation, and death. The organotypic culture system of human fetal colonic epithelial cells seeded on top of collagen gels with embedded colonic fibroblasts allowed prolonged culture of the colonic epithelial cells (Kalabis J, Patterson MJ, Enders GM, Marian B, Iozzo RV, Rogler G, Gimotty PA, Herlyn M. FASEB J 17: 1115-1117, 2003). Herein, we have evaluated the role of endothelin-3 (ET3) and both cognate endothelin recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A previous study has shown that stimulation of the EDNRB in astrocyte induces cAMP response element-binding protein (CREB) and c-fos expression via multiple MAPK signaling pathways, including the extracellular regulated kinase (ERK) 2, c-Jun N-terminal kinase 1 (JNK1), and p38 kinase (38). EDN3 stimulation also rapidly increased phosphorylation of ERK2 in neural progenitor cells (39) and activated IkappaB and MAPK in the human colonic epithelial cells (40). Likewise, EDN3 treatment resulted in the activation of MAPK-p90 ribosomal S6 kinase-CREB and cAMP-protein kinase A-CREB pathways in melanocyte culture (41, 42) and induction of ERK1/2 and focal adhesion kinase (FAK) phosphorylation in malenoma cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that stimulation of the EDNRB in astrocyte induces cAMP response element-binding protein (CREB) and c-fos expression via multiple MAPK signaling pathways, including the extracellular regulated kinase (ERK) 2, c-Jun N-terminal kinase 1 (JNK1), and p38 kinase (38). EDN3 stimulation also rapidly increased phosphorylation of ERK2 in neural progenitor cells (39) and activated IkappaB and MAPK in the human colonic epithelial cells (40). Likewise, EDN3 treatment resulted in the activation of MAPK-p90 ribosomal S6 kinase-CREB and cAMP-protein kinase A-CREB pathways in melanocyte culture (41, 42) and induction of ERK1/2 and focal adhesion kinase (FAK) phosphorylation in malenoma cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has also been applied to the isolation of many other highyield homogenous and viable cells (27). Because of the persistent renewal of human fetal intestinal cells, continuous epithelial cell cultures can be generated relatively easily from the human fetal intestine in a reproducible manner (17,19). Furthermore, the thermolysin method of generating viable HIEC cultures has proven to be particularly useful in the study of normal function and of metabolic and growth mechanisms (7,17,28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the thermolysin method of generating viable HIEC cultures has proven to be particularly useful in the study of normal function and of metabolic and growth mechanisms (7,17,28). Since ET-3 affects the growth and differentiation of gastrointestinal epithelial cells by mediating epithelial-mesenchymal interactions, which control intestinal epithelial growth in the developing mammalian fetus (19), ET-3 was added to stimulate the growth of HIEC. By adding ET-3, the achievement ratio was enhanced again to 60% from only 38% in a previous study (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SW480 cells were transiently transfected with either scramble control or IMP-1 siRNAs, seeded on Type I Collagen embedded with human fetal colonic fibroblasts (ATCC), grown in organotypic culture (OTC), harvested, and fixed as previously described (34). …”
Section: Methodsmentioning
confidence: 99%